Spatial-temporal analysis of the "islands of heat" of the metropolis for satellite images Landsat - Зацерковний, В. І.; Оберемок, Н.В.; Березіна, П.О. (Science-based technologies, 2018)
In this article, a phenomenon and causes of urban heat islands are examined using remote sensing satellite data. An urban heat island is a positive temperature anomaly between a built-up area and surrounding suburban neighborhoods. Landsat 5 ETM + and Landsat 8 satellite imagery of the city of Kiev was acquired for a period of 30 years from 1985 to 2016. These materials were subjected to imagery restoration and processing to obtain earth surface temperature rasters and the normalized difference vegetation index. After comparing with mean temperatures of selected suburban areas, the urban heat island intensity was determined. Noting the change of these temperature anomalies in space and time, possible reasons for urban heat island occurrence were discussed, such as increased building rates, the lack of green space, emissions from transport and production facilities into the atmosphere.